Early Life Nutrient Intake Is Associated with Weight-for-Length Z-Scores at 3 and 12 Months (P11-127-19). (13th June 2019) - Davis, Erin; Musaad, Salma; Monaco, Marcia; Donovan, Sharon
Abstract: Objectives: Rapid weight gain over the first 12 months of life is a risk factor for childhood obesity. While macronutrient concentrations in human milk (HM) or infant formula (IF) have been associated with rapid weight gain or weight-for-length Z-scores later in infancy, few studies evaluate milk intake. Therefore, the objective was to assess how nutrient intake at 6 weeks of age, across multiple feeding modes, influences growth over the first year of life. Methods: Data were collected from 222 healthy mother-infant pairs enrolled in the STRONG Kids 2 Cohort. Twenty-four hour test weighing was conducted to measure milk intake volume and a human milk sample was collected at 6 weeks postpartum. Milk samples were analyzed for total protein (Bradford assay), fat (total lipid extraction), and carbohydrate (Orcinol assay). Mode of feeding at 6 weeks, servings per day of HM and/or IF, and formula type were reported by mothers. For exclusively breastfeeding infants, HM macronutrient concentrations and total intake were used to calculate nutrient intake. For those receiving IF, the numbers of feedings from HM and/or from IF and formula nutrition information were also used to calculate nutrient intake. Infant length and weight collected at study visits were used to calculate weight-for-length Z-scores (WFL-Z). Mixed linear models were used to measure associations between macronutrient intake, total calories, total milk intake and WFL-Z at 3 months and 12 months of age. Models were controlled for 6-week feeding mode, breastfeeding duration, and timing of solid food introduction. Results: At 3 months, WFL-Z was associated with total milk ( P = 0.03) and caloric intake ( P = 0.03) as well as intake of fat ( P = 0.02), carbohydrate ( P = 0.05), and protein ( P = 0.03). WFL-Z at 12 months was associated with protein ( P = 0.02) and fat ( P = 0.04) intakes at 6 weeks but no longer associated with other measures of nutrient intake. Conclusions: Our results support previous findings suggesting that high protein intake in infancy contributes to obesity risk. While milk intake was only quantified once, data show that nutrient intake at 6 weeks-of-age influences future growth. More research is needed to understand other lifestyle and nutritional factors between 3 and 12 months that contribute to growth trajectories and weight during infancy. Funding Sources: National Dairy Council, NIH RO1DK107561, The Gerber Foundation, The Doris Kelley Christopher Foundation.